2019
DOI: 10.1002/ijc.32714
|View full text |Cite
|
Sign up to set email alerts
|

Unique and redundant roles of SOX2 and SOX17 in regulating the germ cell tumor fate

Abstract: Embryonal carcinomas (ECs) and seminomas are testicular germ cell tumors. ECs display expression of SOX2, while seminomas display expression of SOX17. In somatic differentiation, SOX17 drives endodermal cell fate. However, seminomas lack expression of endoderm markers, but show features of pluripotency. Here, we use chromatin immunoprecipitation sequencing to report and compare the binding pattern of SOX17 in seminoma‐like TCam‐2 cells to SOX17 in somatic cells and SOX2 in EC‐like 2102EP cells. In seminoma‐lik… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 44 publications
2
34
0
Order By: Relevance
“…For TFAP2C, the mRNA level was significantly up‐regulated in seminoma compared to non‐seminoma samples and this at least partly suggests that TFAP2C is associated with seminoma to some extent. In fact, the relations between TFAPC2 and seminoma were previously reported 33‐36 . TFAP2C was reported to be associated with chemosensitivity 33 .…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…For TFAP2C, the mRNA level was significantly up‐regulated in seminoma compared to non‐seminoma samples and this at least partly suggests that TFAP2C is associated with seminoma to some extent. In fact, the relations between TFAPC2 and seminoma were previously reported 33‐36 . TFAP2C was reported to be associated with chemosensitivity 33 .…”
Section: Resultsmentioning
confidence: 83%
“…Cell cycle progression is tightly correlated with DNA damage. Studies indicated that when DNA damage occurred, cells either transiently blocked cell cycle progression to spare time for DNA repair or exited the cell cycle 35 . From this point of view, we further checked the DNA damage status of TCam‐2/CDDP cells in the CDDP treatment context after METTL3 overexpression or inhibition and DNA damage was attenuated in the METTL3‐inhibited condition (Figure 3F).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, partnering of SOX2 with PAX6 (instead of OCT3/4) leads to a switch in the function of SOX2 from pluripotency‐promoting to endodermal differentiation‐inducing 38 . Given the high similarity between SOX factors and that SOX2 and SOX17 share similar functions in regulating pluripotency in ECs and seminomas, respectively, it seems reasonable that both factors are able to switch their functions in dependency of the interacting partner 39 . The finding that SOX17 might be a key factor of YST formation strengthens the idea that pYSTs, which do not originate from a GCNIS, arise from an early SOX17+ PGC, where SOX17 switches function as a result of a microenvironment‐triggered FOXA2 induction (Figure 4A) 40 .…”
Section: Discussionmentioning
confidence: 99%
“…We also analyzed the TFAP2C and H3K27ac ChIP-seq data on SVA_D, which showed clear binding of TFAP2C and enrichment of H3K27ac over SVA_Ds in hPGCLC but not in hESC ( Fig S3B). Because the transcriptome of human seminoma-like cell Tcam-2 is similar to human PGCs, and knockdown of SOX17 in Tcam-2 cells has been reported to affect the expression of other important germ cell transcriptional factors, like TFAP2C and NANOG (Irie et al, 2015), we investigated the binding of SOX17 on LTR5_Hs in germline lineage using SOX17 ChIP-seq data in Tcam-2 cell line (Jostes et al, 2020). We observed strong binding of SOX17 on LTR5_Hs as we expected from the binding of TFAP2C ( Fig 3D).…”
Section: Resultsmentioning
confidence: 99%
“…ChIP-seq analysis NANOG ChIP-seq in hPGCLC was from this paper. NANOG ChIP-seq in hESC from GSE105028 (Lyu et al, 2018), TFAP2C ChIP-seq in hESC and hPGCLC, H3K27ac ChIP-seq in hPGCLC were from previous publications GSE140021 (Chen et al, 2019) , H3K27ac ChIP-seq was in hESC hPGCLC from previous publications GSE69646 (Hikabe et al, 2016) and SOX17 ChIP-seq in Seminoma-like cells was from GSE130519 (Jostes et al, 2020). For all ChIP-seq data, quality control was performed by fastqc v0.11.8 (Andrews, 2010).…”
Section: Transcription Factor (Tf) Motif Enrichment Analysismentioning
confidence: 99%